DESIGN OF POTENT ANTICANCER MOLECULES COMPRISING PYRAZOLYL-THIAZOLINONE ANALOGS USING MOLECULAR MODELLING STUDIES FOR PHARMACOPHORE OPTIMIZATION - Raut, Kunal; Kothawade, Sachin; Pande, Vishal; Bole, Sandesh; SAMPADA NETANE; Autade, Kalyani; Joshi, Ashvini (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Numerous tiny receptor tyrosine kinase inhibitors have been reported as anticancer medications over the past 10 years. However, a lot of them lack effectiveness in vivo, selectivity, or do not last long before developing resistance. Methods: We used molecular modeling research to improve the pharmacophore to get beyond these limitations. For the purpose of linking the chemical makeup of pyrazolyl thiazolinone analogs with their anticancer activity, quantitative structure activity relationship (QSAR) investigations in two dimensions (2D) and three dimensions (3D) were carried out. Pyrazolyl thiazolinone pharmacophore’s stearic, electronic, and hydrophobic requirements were calculated using 3D QSAR. Results: By leveraging the findings of QSAR investigations, the pharmacophore was refined and new chemical entities (NCEs) were generated. The r2 and q2 values obtained for the best model No. 4 of 2D QSAR were 0.9244 and 0.8701, respectively. A drug-like pharmacokinetic profile was ensured by studying the binding affinities of proposed NCEs on epidermal growth factor receptor-TK using docking studies and estimating their absorption, distribution, metabolism, and excretion features. Conclusion: When statistical significance is closely examined, predictability of the model and its residuals (actual activity minus predicted activity) is found to be close to zero, leading us to draw the conclusion that the logic behind the design of NCEs was determined to be sound.